Treatment of leachate from Quezon City controlled dumping facility using constructed wetland - Garcia, Raymond Charles A.; Magsino, Calin Ann G.; Resurreccion, Augustus C.; Diola, Ma. Brida Lea D.; Dela Cruz, Edgar Angelo D. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Payatas Controlled Dumping Facility, also known as the Quezon City Controlled Dumping Facility (QCCDF) is the largest operating dumpsite in Metro Manila. Since a fraction of the leachate it generates is directly discharged to surrounding water bodies, it is necessary to treat the wastewater first to avoid possible contamination of surface water as well as groundwater. The objectives of this study include the design and construction of a laboratory-scale constructed wetland that would treat sample leachate from the QCCDF, determination of the percent removal of selected physicochemical characteristics of leachate and assessment of the effluent quality by comparison to existing standards. Fourteen physico-chemical parameters are observed - temperature, pH, total dissolved solids (TDS), turbidity, dissolved oxygen (DO), chemical oxygen demand (COD), ammonia, chloride, nitrate, nitrite, phenols, phosphate, sulfate and zinc concentrations. The set-up is ran and operated with fresh leachate from the QCCDF diluted to a 1:20 ratio. Effluent leachate is tested with retention time of 14 days. At the 14th day, nitrite obtained the highest removal of 95.69% followed by ammonia with 92.82% removal. COD, nitrate and phosphate also produce removal rates of more than 60%. Phenols and zinc in the effluent were both undetected while sulfate and turbidity attained 43.73% and 52.85% removal, respectively. As expected, no concentration reductions were observed for chloride and TDS and no increase in concentration for DO. Comparing to DAO 35 standards, the leachate effluent passes the phenols concentration and TDS (for class B rivers) limiting value and is within the temperature and pH range. As for the EPA Standards for Effluent Discharge Regnlations in Mauritius, nitrite and phenols effluent concentrations are within acceptable limits.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Sanitary landfills -- Leaching; Leachate; Constructed wetlands; Effluent quality -- Standards